Integrating Technology in Islamic Religious Education: Echaning Engagement and Learning Outcomes - Mahmudi, Mohammad Ali (Asosiasi Ide Bahasa Kepri, 2024)
This study aims to explore the impact of technology integration in Islamic Religious Education learning on student engagement and learning outcomes. Along with the development of digital technology, educators are challenged to apply more interactive and adaptive learning methods. This research uses a qualitative approach with a case study method in several schools that have implemented technology in Islamic Religious Education classes. Data was collected through classroom observations, interviews with teachers, and questionnaires to students. The results show that the use of technology, such as learning videos, interactive apps, and e-learning platforms, significantly increases student engagement in the learning process. In addition, there is an increase in student learning outcomes, especially in terms of material understanding and critical thinking skills. This study recommends that technology be more integrated in the Islamic Religious Education curriculum to maximize a more interesting and effective learning experience.